INFLUENCE OF HYDROGEN ON FORMING OF ALLOYS STRUCTURE AT CASTINGS HARDENING - V. Ju. Stetsenko (Литьë и металлургия)
On the basis of analysis of scientific publication it is shown that hydrogen can influence directly on the alloys structure forming at hardening of castings.